Modelo estratégico operativo de responsabilidad social basado en los estándares laborales de los principios del Pacto Mundial de las Naciones Unidas para la empresa Quito INOR Flowers ubicada en el sector de Boliche, parroquia San Juan de Pastocalle, Latacunga-Ecuador - Espinoza Poveda, Elías Wilfrido (2015)
This research has focused on identifying the performance of the functions performed by employees of Quito Inor Flowers, with the purpose to establish a model of social responsibility, which is based on the ten principles of the Global Compact of the United Nations; and thus to improve the environment labor, working conditions and hence the productivity of the organization. In this sense the working conditions of both operational and administrative staff investigated, considering that each of these groups play very different roles, exposing themselves to various characteristics of their jobs conditions, which are exposed operational use chemicals that could affect their health, meanwhile, administrative employees are exposed to stressful jobs; it considering each case takes analyze information through surveys and interview. By obtaining this information from employees of Quito Inor Flowers, general aspects have been considered in this paper, so to establish a model of appropriate responsibility for both the company and employees is evaluated and reach the results sought by the company. Considering the importance given to an organization poses a model of social responsibility to better productivity in this case considering the contributors to the development of this model is intended to add value that will propel each generated which are part of the company and to provide better quality products, based on a job that involves warmth and commitment.